SARS-CoV-2 Nsp5 Demonstrates Two Distinct Mechanisms Targeting RIG-I and MAVS To Evade the Innate Immune Response - Yongzhen Liu (American Society for Microbiology, 2021)
The ongoing COVID-19 pandemic is caused by SARS-CoV-2, which is rapidly evolving with better transmissibility. Understanding the molecular basis of the SARS-CoV-2 interaction with host cells is of paramount significance, and development of antiviral agents provides new avenues to prevent and treat COVID-19 diseases. This study describes a molecular characterization of innate immune evasion mediated by the SARS-CoV-2 Nsp5 main protease and subsequent development of a small-molecule inhibitor.